The knowledge and professional attitudes toward denture adhesives in Mosul - Nadira A Hatim; Hala K Ali; Hydar M Shindala (University of Mosul, College of Dentistry, 2011)
Aims: The aims of the present study is evaluate the dentist knowledge and believes toward denture adhesive through generation of discussion among dentist (in ministry of health and ministry of higher education) in Mosul city. Materials and Methods: In a dental meeting that held on April 2009 in College of Dentistry ,university of Mosul ,a questionnaire paper was given to 264 dentist which consist of two: part the first one evaluate dentist knowledge about denture adhesive, the second one evaluate the dentist attitude toward denture adhesive. Result: The findings of the present study showed that (9.8%, 67.8% and 22.4%) of dentists had respectively weak, moderate and good knowledge toward denture adhesive while( 3.1%, 80.4% and 16.6%) had respectively negative, moderate and positive attitude toward denture adhesive materials. The 2 test showed non significant statistical relation between dentist knowledge about denture adhesives and their previous years of experience, place of work, sex and their degree of education. Statistical analysis methods used to analyze and asses the result of this study were SPSS version 13.0. Conclusions: The findings of the present study showed that dentist knowledge and attitude toward denture adhesive materials was moderate. Their information about denture adhesive indications, contraindications, advantages and disadvantages were very poor therefore prosthodontic specialist in College of Dentistry, University of Mosul should insist on denture adhesive in student's curriculum with increasing the credit hours.